Nighttime screen use, sleep quality, and smartphone addiction symptoms among medical students: an international cross-sectional study - Liebig, Lukas; Balogh, Erika; Birkás, Béla; Faubl, Nóra; Zelko, Erika; Gräfe, Willy; Pieper, Sophie; Gottschall, Mandy; Riemenschneider, Henna (Frontiers in Psychiatry, 2026)
BackgroundNighttime screen use is associated with poor sleep and may represent an emerging public health concern. Medical students are a vulnerable group for harmful health behaviour due to demanding studies, while also playing a key role in future health promotion. The study examined the prevalence of nighttime screen use among medical students in different countries and explored associations with sleep and smartphone addiction symptoms.MethodsThe Medical Student Health Survey, an international cross-sectional study, was conducted at four sites in Germany (GER), Austria (AU), Hungary (HU), and Japan (JA). Nighttime screen use was assessed via five self-developed items, sleep via Pittsburgh Sleep Quality Index (PSQI), and smartphone addiction symptoms via Smartphone Addiction Scale–Short Version (SAS-SV). Group differences were tested using chi-square, Welch’s t-test, Z-test, and Kruskal–Wallis test (Bonferroni-adjusted), and associations were evaluated using Kendall’s tau-b and a multivariable binary logistic regression model.ResultsData from n = 1,262 medical students (mean age 21–24, 56%–73% female) were analysed. The median pre-bedtime screen use was 30 minutes, and the median end of use was between 5 and 10 minutes before bedtime. Approximately 96%–98% used a screen within 1 hour of bedtime; 69%–89% used a smartphone/tablet. SAS-SV scores ranged from M = 23.2 (HU) to M = 27.0 (JA), and the prevalence of smartphone addiction ranged from 12.6% (GER) to 27.9% (JA). PSQI scores ranged from M = 4.33 (JA) to M = 5.22 (HU), and prevalence of poor sleep quality ranged from 25% (JA) to 40.7% (HU). Prolonged pre-bedtime screen use was associated with increased sleep latency (τ = 0.106, p <.001), shorter distance between the end of screen use and bedtime, and increased SAS-SV scores (τ = −0.150, p <.001). Screen use after waking up at night was associated with poorer sleep quality (τ = 0.174, p <.001), poorer outcome in five of seven PSQI subscales (all τ > 0.1, p <.001), and increased SAS-SV scores (τ = 0.165, p <.001). Sleep disturbance by a device was associated with poorer sleep quality (τ = 0.170, p <.001), poorer outcome in three of seven PSQI subscales (all τ > 0.1, p <.001), and increased SAS-SV scores (τ = 0.135, p <.001). In the logistic regression, screen use after nocturnal awakenings and device-related sleep disturbance remained independently associated with poor sleep quality (all p ≤.04), whereas smartphone addiction symptoms showed no independent association.ConclusionsThe findings highlight the need for targeted interventions to promote health-conscious screen use among medical students.